LITERATUR REVIEW : Efektifitas Ekstrak Umbi Bawang Dayak (Eleutherine palmifolia L.) dalam Menghambat Pertumbuhan Bakteri Staphylococcus aureus - Nia P.S Nainggolan; Ratna Widayati; Dian Mutiasari (Fakultas Kedokteran, Universitas Palangka Raya, 2021)
According to who one-third of the 25 million deaths worldwide are caused by infectious diseases. One of the bacteria that most often causes infection is Staphylococcus aureus. Herbal plant onion dayak (Eleutherine palmifolia L) contains compounds that are efficacious as antibacterial, one of which is the bacterium Staphylococcus aureus. Objective: analyze the effectiveness of dayak onions (Eleutherine palmifolia L) in inhibiting the growth of Staphyloccus aureus bacteria. This research is a literature research with a sample of research in the form of national journals obtained 10 from Google Cendikia, Garuda while international journals obtained 5 from Google Scholar and Science Direct. A journal that discusses the effectiveness of dayak onions (Eleutherine palmifolia L) in inhibiting the growth of Staphylococcus aureus bacteria, found 15 journals that state that the tubers of onion dayak (Eleutherine palmifolia L.) have the ability to inhibit the growth of Staphylococcus aureus bacteria. In thejournal studied also discussed about the factors that affect the effectiveness of onion dayak (Eleutherine palmifolia L) in inhibiting the growth of bacteria including the temperature and length of storage of extracts. Dayak onions (Eleutherine palmifolia L) have effectiveness in inhibiting the growth of Staphylococcus aureus bacteria.